Add-on iguratimod as a therapeutic strategy to achieve remission in patients with rheumatoid arthritis inadequately responding to biological DMARDs: A retrospective study. Issue 2 (4th March 2018) - Yoshikawa, Ayaka; Yoshida, Shuzo; Kimura, Yuko; Tokai, Nao; Fujiki, Yohei; Kotani, Takuya; Matsumura, Yoko; Takeuchi, Tohru; Makino, Shigeki
Abstract: Objectives: In this study, iguratimod (IGU) was added to rheumatoid arthritis (RA) patients inadequately responding to 24-week or longer treatment with biological disease-modifying antirheumatic drug (bDMARDs), its effectiveness was assessed, and factors contributing to remission were evaluated. Methods: RA patients who fulfilled the following criteria were included: (i) ≥ 24-week of bDMARDs; (ii) 2.6 < disease activity score (DAS) 28-erythrocyte sedimentation rate (ESR) < 5.1 or the presence of synovitis with a power Doppler (PD) score ≥2 in at least 1 of the 28 joints on joint ultrasonography. Disease activity and joint ultrasound findings were evaluated at baseline and at 12 and 24 weeks. Results: DAS assessing 28 joints with ESR (DAS28-ESR) decreased significantly from 3.45 ± 0.92 at baseline to 2.85 ± 1.13 at 24 weeks ( p  < .001). Overall, 38.3% achieved clinical remission (c-remission). The total PD score decreased significantly from 8.7 ± 6.1 at baseline to 5.5 ± 5.0 at 24 weeks ( p  < .001). A lower baseline DAS28-ESR was related to c-remission after 24 weeks ( p =.002). Shorter duration of disease ( p =.020) was related to ultrasound remission, in addition to a lower baseline DAS28-ESR ( p  < .001). Conclusions: IGU add-on therapy can be a therapeutic strategy to achieve remission in RA patients inadequately responding to ≥24-week treatment with bDMARDs.